Role of the agrarian associationism in the context of citrus crisis:comments on the lemon sector in the province of Malaga - Natera Rivas, Juan José; Larrubia Vargas, Remedios (Anales de Geografía de la Universidad Complutense, 2010)
Lemon sector in Malaga is crossing a stage of crisis, which takes place in a context of an increase of the requirements, on the part of the buyers, related to trazability, quality, aspect, etc., of the fruit. The accomplishment of those requirements is difficult for the productors, due to the reduced size of their orchards, among other reasons. Due to this, Associative Agrarian Entities can perform a role of great importance, stimulating initiatives tending to improve the possibilities of their partners to be kept in the activity. Nevertheless, not all the Entities have started some initiative and, those that have done it, have cosen among different options, as response to the characteristics of their partners. The identification and characterization of these actions, with important consequences on the continuity in the activity of their partners, is the aim of this paper.
Keywords: Associative Agrarian Entities; Citrus; Lemon; Malaga